Adult Student Expectations and Experiences in an Online Learning Environment. Issue 3 (1st September 2016) - Bourdeaux, Renee; Schoenack, Lindsie
Abstract: This study investigated adult student experiences with instructors in online classes. Using expectancy violations theory as a lens, we conducted 22 interviews to understand reasons students enroll in online classes, expectations for instructors, and behaviors instructors employed that may or may not meet expectations. We conducted a thematic analysis and uncovered students expected clarity, respect, and intentional course design from instructors. Behaviors facilitating effective communication and enabling learning actually led to positive outcomes, while the poor use of pedagogical tools and behaviors stopping the learning process led to negative outcomes. Recommendations to meet adult student needs online are proposed.